Adobe Illustrator CC : learn by video - Chelius, Chad (Peachpit Press, 2013)
"This critically acclaimed training program from Adobe Press offers high-definition video to teach the fundamentals of Illustrator CC. Experienced instructor Chad Chelius presents a comprehensive introduction to Illustrator, including best practices as well as fundamental illustration and vector artwork concepts. Covered topics include working with styles, paths, and objects, and how to work within the Creative Cloud. Crucial to the training are optimized teaching methods, practical tips, and the focus on learning by doing with project files."--Resource description page.